1997
DOI: 10.1115/1.2815580
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Oscillation Control by Cyclic Fuel Injection

Abstract: A number of recent articles have demonstrated the use of active control to mitigate the effects of combustion instability in afterburner and dump combustor applications. In these applications, cyclic injection of small quantities of control fuel has been proposed to counteract the periodic heat release that contributes to undesired pressure oscillations. This same technique may also be useful to mitigate oscillations in gas turbine combustors, especially in test rig combustors characterized by acoustic modes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…In particular, we have shown that the same proposition that explained the idea behind stabilization using the switching strategy in [1,2] provides the analytical basis for the results in [4,5] as well. We showed that our observations based on the model and the proposition matches the experimental observations in [4,5].…”
Section: å ¡mentioning
confidence: 78%
See 4 more Smart Citations
“…In particular, we have shown that the same proposition that explained the idea behind stabilization using the switching strategy in [1,2] provides the analytical basis for the results in [4,5] as well. We showed that our observations based on the model and the proposition matches the experimental observations in [4,5].…”
Section: å ¡mentioning
confidence: 78%
“…It should be noted that the combustor in [1] differs from that in [2] in two respects. First, variations in ¦ t a re present in the rig in [1], contrary to the case in [2] where a decoupler is introduced between the feed system and the burning zone. This implies that the time-delay in [1] may be due to t…”
Section: å ¡mentioning
confidence: 99%
See 3 more Smart Citations